Mucosal Phenotype as A Multidisciplinary Approach: A Narrative Review - Ibrahim, Malik (Khalij-Libya Journal of Dental and Medical Research, 2024)
Objectives: The Gingival phenotype (GPh) or soft-tissue periodontal phenotype is critical for decision making during treatment planning and aesthetic outcomes in several fields of dentistry. The aim is to bring and summarize the crucial literature about GPh. Data: Data was collected according to: title of article, study design, and keywords. Method: Searching the Medline database (PubMed) and complementing by manual searches to better reaching the important primary and secondary type of studies. The result of search is reported by PRISMA flow-diagram. Conclusion: As one of the major risk factors of peri-implant inflammation is GPh; Careful diagnosis of GPh at the time of tooth replacement may prevent from developing mucogingival defects, or recession following periodontal and orthodontic treatment. Gingival phenotype has inter-individual and intra-individual variation; Thicker GPh is in molars rather than premolars and incisors, and in maxillary teeth rather than in mandibular and modifying GPh is becoming a trend through the use of Hyaluronic Acid (HA) or Injectable-Platelet Rich Fibrin (i-PRF) with microneedling as a minimally invasive therapy. Skeletal class (I and III) and labial inclined lower central incisors are strongly associated with thin GPh. BOP is increased in thin GPh while thicker GPh has more pocket depths. Thin GPh predicts a thin antral-mucosal thickness and vice versa. Clinical significance: Determination of GPh during routine examination is likely to be crucial to overcome unwanted outcomes after several interventions, as nowadays, the aesthetic outcome following any dental procedure is being a trend and critical for both clinicians and patients’ satisfaction. الأهداف: يعتبر النمط الظاهري اللثوي أو النمط الظاهري للثة والأنسجة الرخوة أمرًا بالغ الأهمية لاتخاذ القرارات أثناء تخطيط العلاج والنتائج الجمالية في العديد من مجالات طب الأسنان. الهدف هو جمع وتلخيص الأدبيات المهمة حول النمط الظاهري اللثوي. البيانات: تم جمع البيانات وفقًا لما يلي: عنوان المقالة وتصميم الدراسة والكلمات الرئيسية. الطريقة: البحث في قاعدة بيانات ميدلاين واستكمالها بالبحث اليدوي للوصول بشكل أفضل إلى النوع الأساسي والثانوي المهم من الدراسات. تم الإبلاغ عن نتيجة البحث من خلال مخطط تدفق PRISMA. الخلاصة: نظرًا لأن أحد عوامل الخطر الرئيسية للالتهاب حول الزرع هو التهاب اللثة حول الزرع؛ فإن التشخيص الدقيق لالتهاب اللثة حول الزرع في وقت استبدال الأسنان قد يمنع حدوث عيوب مخاطية لثوية أو انحسار بعد علاج اللثة وتقويم الأسنان. النمط الظاهري للثة له تباين بين الأفراد وداخل كل فرد؛ ويوجد التهاب الغشاء المخاطي اللثوي في الأضراس أكثر من الضواحك والقواطع، وفي الأسنان الفكية أكثر من الفك السفلي وأصبح تعديل التهاب الغشاء المخاطي اللثوي اتجاهًا من خلال استخدام حمض الهيالورونيك أو الفيبرين الغني بالصفائح الدموية القابلة للحقن (i-PRF) مع الوخز الدقيق كعلاج طفيف التوغل. ترتبط فئة الهيكل العظمي (الأول والثالث) والقواطع السفلية السفلية المائلة الشفوية ارتباطًا وثيقًا بالـ GPh الرقيق، ويزداد ضغط الدم في الجيوب الرقيقة بينما يكون للـ GPh الأكثر سمكًا عمق جيب أكبر. يتنبأ الغشاء المخاطي الغشائي الرقيق بسماكة الغشاء المخاطي الجيبي الانفي والعكس صحيح. الأهمية السريرية: من المرجح أن يكون تحديد درجة حرارة الجسم أثناء الفحص الروتيني أمرًا حاسمًا للتغلب على النتائج غير المرغوب فيها بعد عدة تدخلات، حيث أن النتيجة الجمالية بعد أي إجراء للأسنان في الوقت الحاضر أصبحت اتجاهًا وحاسمًا لكل من الأطباء السريريين ورضا المرضى.